System Implementation, Evaluation Methods, Utilization of Results, and Effectiveness of the Performance Evaluation System at the Refinery - Arif Indra Nugraha; Isnurhadi; Mu'izzuddin; Wita Farla WK; Yomeini Margareth (Cakrawala Repositori IMWI)
Performance appraisal systems often appear procedurally complete; however, their effectiveness does not always result from the completeness of these stages alone. This study analyzed the effects of performance appraisal system implementation and performance appraisal methods on the effectiveness of the employee performance appraisal system, with the utilization of performance appraisal results as a mediating variable. The research was conducted at PT X, one of the processing units (refineries) of an energy company operating in the oil and gas processing sector in Indonesia, an industry that requires work precision, safety compliance, cross-functional coordination, and operational reliability. Data were collected through questionnaires distributed to 72 employees and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS. The results showed that performance appraisal methods had positive and significant effects on the utilization of performance appraisal results and the effectiveness of the employee performance appraisal system. The utilization of performance appraisal results also had a positive and significant effect on the effectiveness of the employee performance appraisal system. In contrast, the implementation of the performance appraisal system had a positive but statistically insignificant effect. The mediation analysis revealed that the utilization of performance appraisal results mediated the relationship between performance appraisal methods and the effectiveness of the employee performance appraisal system but did not mediate the relationship between performance appraisal system implementation and the effectiveness of the employee performance appraisal system.